An Experience of Carcinoma Tongue - Muhammad Ashfaq, Mirza Khizer Hameed, Zeeshan Ayub, Kamran Ashfaq (Journal of Rawalpindi Medical College, 2013)
Background : To determine the demography, risk factors, clinical profile and surgical procedures performed in patients of squamous cell carcinoma tongue. Methods: In this descriptive study 95 patients of squamous cell carcinoma tongue, diagnosed on histopathology were evaluated. Demographic profile, risk factors, sites of distribution and nodal involvement were noted. The surgical procedures were adopted in accordance with the stage of disease Results: Majority (74.7%) were male. The average age of presentation was 55 years with age range of 28- 81 years. Majority(71.6%) had one of the known risk factors.Lateral border of tongue(73.7%) was the commonest site involved. Primary disease with negative nodes was found in 53.7%. Partial/ hemiglossectomy with supraomohyoid neck dissection was carried out in 57.9% with early disease (Stage I & II), while hemiglossectomy / subtotal glossectomy with radical neck dissection was carried out in 33.7% with advanced disease (Stage III & IV). Conclusion: Squamous cell carcinoma tongue is three times more common among males of relatively advanced ages. Known risk factors such as tobacco, betel quid and ‘naswar’ have a strong association with squamous cell carcinoma. Lateral border of tongue is the commonest site of involvement. Primary tumour surgery is combined with some form of neck dissection depending upon the involvement of neck nodes.